Investigating the impacts of COVID-19 among LGBTQ2S youth experiencing homelessness - Abramovich, Alex; Pang, Nelson; Moss, Amanda; Logie, Carmen H.; Chaiton, Michael; Kidd, Sean A.; Hamilton, Hayley A. (PloS one, 2021)
LGBTQ2S youth are overrepresented among youth experiencing homelessness and experience significantly higher rates of mental health issues compared to heterosexual and cisgender youth. COVID-19 related challenges for LGBTQ2S youth experiencing homelessness remain unknown. To address this gap, this study aimed to understand the impacts of the COVID-19 pandemic on LGBTQ2S youth at risk of, and experiencing, homelessness in the Greater Toronto Area, Ontario, Canada and surrounding areas. Utilizing a mixed-methods convergent parallel design, LGBTQ2S youth experiencing homelessness were recruited to participate in virtual surveys and in-depth one-on-one interviews. Surveys included standardized measures and were administered to measure mental health outcomes and collect information on demographic characteristics, and health service use. Survey data were analyzed with descriptive statistics and statistical tests for difference of proportions. Interviews were analyzed using an iterative thematic content approach. Sixty-one youth completed surveys and 20 youth participated in one-on-one interviews. Quantitative and qualitative data showed that youth have been significantly impacted by the COVID-19 pandemic in various ways, including experiencing poor mental health, such as suicidality, depression, anxiety, and increased substance use, and lack of access to health and social support services. Our study highlights the need for LGBTQ2S inclusive and affirming health care and support services for precariously housed adolescents to address the pre-existing social and health issues that have been exacerbated by the pandemic.